Varied EMG responses of the quadriceps muscle during a Wingate anaerobic test - Okano, Alexandre Hideki; Moraes, Antonio Carlos de; Bankoff, Antonia Dalla Pria; Cyrino, Edilson Serpeloni; Simões, Herbert Gustavo; Pezarat-Correia, Pedro; Barbieri, João Francisco; Teodoro, Cássia Lopes; Gáspari, Arthur Fernandes (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The Wingate Test (WAnT) has been used to evaluate anaerobic performance in cycle ergometer. Objective: The purpose of the present study was to analyze the EMG response of the superficial quadriceps femoris muscles during the Wingate anaerobic test (WAnT). In addition, we investigated the influence of these muscles in performance and fatigue during the WAnT. Methods: For this purpose eight male cyclists performed a 30-s WAnT. Electromyographic amplitude (RMS) and median power frequency (MPF) data of the vastus lateralis (VL), vastus medialis (VM), and rectus femoris (RF) muscles, performance index (mean power, MP) and rate of fatigue (fatigue index, FI) were recorded during the test; and compared along six time points. The correlation between EMG data and performance parameters were made. Results: No significant differences were found in maximal EMG amplitude for all the muscles. TheMPF of the VL and VM muscles decreased throughout the test (12% and 13%, respectively), however, the decline for the RF was twice greater (25%). Correlation among MP and EMG amplitude was observed only for VL (r=0.83; P<0.01). There was significant correlation between the FI and the MPF decrease in the RF muscle only (r=0.78; P<0.05). Conclusion: During the WAnT, MPF decrease of RF muscle was significantly larger when compared to the VL and VM. The VL muscle electrical activity was positively correlated with MP, suggesting that VL is an accurate predictor of the performance in the WAnT. The MPF decrease of the RF muscle was positively correlated to the FI. These results may be explained by differences in the fiber type composition, biomechanics and architecture properties of these muscles.